METHOD OF ATTRIBUTIVE SIGNS FORMALIZATION - B. I. Bachkalo; V. I. Zolotykh (Научный вестник МГТУ ГА)
According to the official statistics, the reasons of the majority of air incidents which have happened to state aircraft are caused by displays of so-called human factor of the aviation specialists participating in flights operation, as a rule, by negative displays of personal factor of the flight crew during preparation and performance of the flight task. At the same time, the record of “human factor” effect on the security of the aviation system is fragmentary and doesn’t have systematic basis nowadays. This is the factor which prevents the application of systematic approach to the problem of human factor impact on flight safety. In this regard, in order to reduce the impact of personal factor on the safety of the upcoming flight it is necessary to estimate it in terms of quantity. The solution of this task will require defining a number of the most essential personal safety indicators of the pilot, before the upcoming flight and determine the amount of each specific one. But the indicators of pilot’s personal factor potential threat to the safety of the upcoming flight are among the causal phenomena, which signs are not amenable to accurate quantitative estimation. Therefore, the greatest difficulty is in determination of the weight fraction of each hazard indicator according to “personal factor” of the pilot. In order to find solution to this problem, it is necessary to have an evaluation mechanism which will allow to assess the degree of influence of the phenomena on the object of their impact, the signs, which cannot be accurately quantified. Due to the lack of assessment tools known to the authors, which fully meet the stated requirements and allow to solve the problem, the authors developed a new method which enables to quantify the impact of the related phenomena on the subject of the study that do not have numerical expressions.